Using Digital Games to Improve Students' Vocabulary Mastery: A Classroom Action Research at SD IT Permata Insani Islamic School Kota Jambi - Makrub, Makrub (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
This research aimed to (1) identify whether digital games can improve students' vocabulary mastery abilities, and (2) to determine students' interest in learning vocabulary mastery using digital games. This research was conducted at SD IT Permata Insani Islamic School. This research was conducted in August–September 2023 through Classroom Action Research. It consists of two cycles, each cycle had four meetings. There are two types of data in this research, namely qualitative and quantitative data. Qualitative data was obtained by conducting direct observations in the classroom. Questionnaires, documentation and field notes were also used in conducting research. Quantitative data was student scores obtained from the test in each cycle. In analyzing quantitative data, descriptive statistics are used. In analyzing qualitative data, It is involved; (1) Data Reduction (2) Data Display (3) Drawing conclusions and verification. The research results showed that: 1) digital games improve students' vocabulary mastery. The increase of students’ vocabulary mastery can be seen from the average score of the previous semester of 54.00; test 1 in the first cycle was 60 and the average of test 2 in the second cycle was 73. 2) Digital game techniques applied in class can also increase students' interest, interaction, self-confidence and motivation in class activities. Based on research results, teaching vocabulary using digital game methods is a suitable technique for improving students' vocabulary mastery. This study can be used as a reference for teachers in improving the quality of teaching by implementing techniques to improve students' vocabulary mastery abilities.